PENGARUH WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH KOMITMEN AFEKTIF - Nurani, Asima; Nilawati, Levi (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2016)
This study examined the relationship between work life balance on theperformance. This research also examined the mediating role of affective commitment in a retail company in Jakarta. To fi nd answers to these problems researchers distribute a questionnaire consisting of 10 questions about work life balance, six questions about affective commitment, and 11 questions about the performance of employees to 50 employees. The sampling method used is convenience sampling. The data were processed using path analysis with statistical methods SPSS 17.0 for Windows. Basedon the results obtained path analysis, it can be concluded that the affective commitment does not mediate the relationship between work life balance to employee performance, but the direct effect proved.